Functional Nanostructures Processing, Characterization, and Applications - Seal, Sudipta; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
Nanocrystalline materials exhibit outstanding structural and mechanical properties. However, future progress in this emerging field is critically dependent upon the development of new methods of understanding and analyzing the underlying nanoscale and interface effects causing their unique mechanical properties. This exceptionally well- researched volume in Nanostructure Science and Technology serves both as an introduction to structural nanocrystalline materials as well as a monograph providing a systematic overview of the current state-of-the-art of fundamental and applied research in the area. The book provides a unique interdisciplinary approach by incorporating chapters from contributors from various academic disciplines including Engineering, Physics, Chemistry, and Polymer Science. Sudipta Seal integrates the most current and relevant technologies in the field to address the subject. This volume will prove to be indispensable to professionals in the in the field of nanomaterials science and nanotechnologies, from researchers and graduate students to engineers who are involved in production and processing of nanomaterials with enhanced physico-chemical properties.
Advanced Ceramics and Nanocomposites of Half-metallic Ferromagnetic CrO2 for Magnetic, GMR and Optical Sensors -- Functional Nanostructured Thin Films -- MEMS for Nanotechnology: Top-down Perspective -- Nanostructured Biomaterials -- Self-Assembly and Supramolecular Assembly in Nanophase Separated Polymers and Thin Films -- Nanostructures: Sensor and Catalytic Properties -- Nanostructured High-Anisotropy Materials for High-Density Magnetic Recording -- High-Resolution Transmission Electron Microscopy for Nanocharacterization -- Applications of Atomic Force Microscope (AFM) in the Field of Nanomaterials and Nanocomposites.
Keywords: Materials science; Polymers; Solid state physics; Electronics; Microelectronics; Biomaterials; Nanotechnology; Materials Science; Nanotechnology; Materials Science, general; Biomaterials; Polymer Sciences; Electronics and Microelectronics, Instrumentation; Solid State Physics; Electronic books